Mobile Application Design for Protecting the Data in Cloud Using Enhanced Technique of Encryption - Ali Pitchay, Sakinah; Abdo Ali Alhiagem, Wail; Ridzuan, Farida; Perumal, Sundresan (International Journal of Engineering and Technology, 2018)
This paper provides an enhanced technique for improving the security and protecting the privacy of the cloud computing users by encrypting the data before it reached to serverâ€™s storage. Encrypting means the process of converting information or data into unreadable language to prevent unauthorized access. This paper will propose a mobile application design, which will allow the user to encrypt and decrypt the data hence maintaining security and privacy. In the proposed system design, the AES Algorithm will handle the encryption of the data using a keyword which will be defined by the user during the creation of the account. The encryption keyword will be hashed by the system using MD5 Algorithm. The keys will remain in encrypted form, while they are on the server side. Both encrypted data, encryption and decryption keys will be saved on the server in secured form. The idea behind hashing the encryption keys is to protect the keys while they are stored on the server, therefore, any unauthorized access to the server will gain no advantages since every bit of data on the server is encrypted including the private keys. The proposed system design will participate by improving the security and privacy of the users by giving them the capability to encrypt and decrypt data in enhanced way using AES as a data encryption method and MD5 hash algorithm for encrypting the encryption keys.Â Â